Redefining Teaching Itself: A Book Review of The Reflective Educator's Guide to Classroom Research 3rd Edition. - Suzanne Porath (Networks: An Online Journal for Teacher Research, 2017)
The journey metaphor is a typical representation of teacher research and the authors of The Reflective Educator’s Guide to Classroom Research evoke the metaphor, with images of paths, maps and compasses, because it visibly represents the feeling of starting an action research project. The authors make a point to favor the term “inquiry” over “research” to negate the typical associations with the term research.